Implementation of Rational Emotive Behavior Therapy in Children with Emotional Disorders in Pakpak Bharat - Epa Gracelia Ferals Sitorus; Dorlan Naibaho (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
This study aims to describe the use of Rational Emotive Behavior Therapy (REBT) on a child experiencing emotional disturbances following the death of her mother. Healthy psychological development in children plays a crucial role in their ability to learn and adapt. Good cognitive and emotional development enables children to understand and manage their emotions, communicate effectively, and build positive social relationships. A child with strong emotional skills tends to be more resilient, better able to cope with stress, and has a higher level of life satisfaction. This study employs a qualitative case study design to gain an in-depth understanding of individual experiences within a specific context. Observations and interviews were conducted with the subject, a 10-year-old girl named Icha, who was identified as having emotional and behavioral issues suitable for REBT intervention. Romans 12:2 provides relevant spiritual guidance in the context of children's psychological development, emphasizing the importance of transforming the mind for a better life. Through the stages of REBT, Icha successfully identified and changed the irrational thoughts that caused her emotional disturbances. Significant changes were observed in the fourth session, where Icha became calmer and was able to accept herself. This therapy demonstrates the effectiveness of REBT in addressing emotional disorders in children, especially those experiencing trauma from loss.